Let f ( x ) = x 3 + x 2 − 2 x − 1 . If f ( a ) = 0 , find f ( a 2 − 2 ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
nice question :) and nice solution too :)
You might anticipate that a 6 − 5 a 4 + 6 a 2 − 1 is a factor of a 3 + a 2 − 2 a − 1 by using polynomial division. Indeed it is and the other factor is a 3 − a 2 − 2 a + 1 . So f ( a 2 − 2 ) = ( a 3 − a 2 − 2 a + 1 ) ∗ f ( a ) = ( a 3 − a 2 − 2 a + 1 ) ∗ 0 = 0 . Love your questions, sir!
Sorry but i am unable to understand how u took a^2 common from (a^4-3a^2...) step 3 to 4 and 4 to 5 i cannot comprehend.
Problem Loading...
Note Loading...
Set Loading...
From f ( a ) = 0 we get 1 = x 3 + x 2 − 2 x . Through a series of substituting for the constant and subsequent factoring we get:
f ( a 2 − 2 ) = ( a 2 − 2 ) 3 + ( a 2 − 2 ) 2 − 2 ( a 2 − 2 ) − 1 = a 6 − 5 a 4 + 6 a 2 − 1 = a 6 − 5 a 4 + 6 a 2 − a 3 − a 2 + 2 a
= a ( a 5 − 5 a 3 − a 2 + 5 a + 2 )
= a 2 ( a 4 − 3 a 2 + a + 1 )
= a 3 ( a 3 + a 2 − 2 a − 1 )
= a 3 f ( a ) = 0 .